Bilateral cricoarytenoid joint involvement in rheumatoid arthritis: A case report [4] - Kamanli, A.; Gok, U.; Sahin, S.; Kaygusuz, I.; Ardicoglu, O.; Yalcin, S. (My University, 2001)
[Abstract Not Available]
Keywords: Anti-Inflammatory Agents, Non-Steroidal; Antirheumatic Agents; Arthritis, Rheumatoid; Arytenoid Cartilage; Cricoid Cartilage; Female; Humans; Injections, Intra-Articular; Laryngeal Diseases; Middle Aged; Prednisolone; Tracheostomy; gold; methotrexate; nonsteroid antiinflammatory agent; prednisolone; steroid; adult; anamnesis; case report; clinical feature; cricoid; disease severity; female; human; laryngoscopy; larynx; larynx cartilage; letter; physical examination; priority journal; rheumatoid arthritis; synovitis; tracheostomy; vocal cord; voice